A copolymer barrier nylon and its continuous synthesis method and application
By copolymerizing the m-phenylenediamine adipic acid salt with caprolactam in the nylon film, and adding organically coupled nanomontmorillonite and long carbon chain nylon salt, the problem of insufficient barrier properties of the existing nylon film is solved, and copolymerization barrier nylon with high strength, good resistance and good barrier properties is achieved, which is suitable for food packaging.
Patent Information
- Application Number
- CN202210445642.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-26
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2042-04-26
AI Technical Summary
The barrier properties of the existing nylon films are not sufficient to meet the demand for long-term preservation, and the existing high barrier materials such as MXD6 and EVOH are expensive, and uneven dispersion during the blending and extrusion process lead to uneven barrier properties.
Copolymerized nylon was synthesized by using m-phenylenediamine adipic acid (monomer of MXD6) and caprolactam, and organically coupled nanomontmorillonite was added to improve barrier properties, while long carbon chain nylon salt was added to improve toughness and impact strength.
It has achieved high strength, cooking resistance, puncture resistance and good temperature resistance copolymerization barrier nylon, with good barrier properties, and simple process and low cost, which is suitable for industrial production.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to a copolymer nylon and a continuous synthesis method and application thereof, and in particular to a copolymer barrier nylon and a continuous synthesis method and application thereof. Background Art
[0002] Nylon film has the characteristics of puncture resistance, cooking resistance, and good barrier properties, and is widely used in food packaging. In addition to cooked food, live seafood, cooking condiments, high-end rice, flour, noodles, etc. are all packaged with nylon composite film. However, the barrier properties of ordinary nylon film cannot meet the requirements of long-term preservation, and the market is eager for high-barrier cling film. The currently developed MXD6 nylon resin has excellent barrier properties, but it is difficult for the market to accept it due to its high price. EVOH has good barrier and preservation properties, but its resistance to cooking, puncture resistance, and temperature resistance are incomparable to nylon film, and the price is also very high. People also tried to prepare barrier nylon film by blending MXD6 and PA6 by blow molding, but due to the uneven dispersion of MXD6 during the blending extrusion process, its barrier properties are uneven or the barrier effect is poor. Therefore, the barrier properties of food packaging films have always plagued the development of the industry.
[0003] CN106832907A discloses a high shrinkage biaxially stretched nylon 6 film and a manufacturing method thereof, wherein PA6 resin is used as the main base material, and MXD6 or PA612, PA610 special nylon and anti-adhesion agent are added to prepare a barrier, puncture-resistant and impact-resistant film by co-mixing and extrusion. However, this method of directly melt-blending and extruding a biaxially stretched film has the problem of uneven dispersion of the special nylon resin, resulting in uneven film performance.
[0004] CN110641107A discloses an antibacterial high barrier nylon film and its preparation method, which uses PE inner layer, TIE resin as binder, PA6 as outer layer, EVOH as middle layer, and prepares barrier packaging film by multi-layer co-extrusion method. Although this multi-layer co-extrusion process for preparing barrier film can prepare barrier film, it is difficult to ensure the bonding strength between different resins, and there is peeling between the composite film layers, which further affects the uneven strength of the composite film; at the same time, due to the excessive use of polyolefin resin, the puncture resistance and temperature resistance of the composite film are far inferior to those of nylon film, and cannot meet the needs of some high temperature resistant retort packaging.
[0005] CN113881221A discloses a high barrier nylon blend material, which is prepared by blending 60-100 parts of nylon, 10-30 parts of ethylene-vinyl alcohol copolymer, 10-20 parts of montmorillonite, 1-5 parts of antibacterial agent, and 1-3 parts of dispersant. Although ethylene-vinyl alcohol copolymer has good barrier properties, it has poor compatibility with nylon resin, which will seriously affect the mechanical properties of the nylon blend material and even cannot be blended and extruded into a film. Therefore, it is difficult to prepare a barrier film with this blend material.
[0006] Therefore, it is urgent to develop a barrier nylon resin with high strength, cooking resistance, puncture resistance, good temperature resistance and good barrier properties to meet the urgent needs of food packaging, which is also of great significance to promote the technological progress of the packaging film industry. Summary of the invention
[0007] The technical problem to be solved by the present invention is to overcome the above-mentioned defects of the prior art and provide a copolymer barrier nylon with high strength, resistance to boiling and puncture, good temperature resistance and good barrier properties.
[0008] The technical problem to be further solved by the present invention is to overcome the above-mentioned defects of the prior art and provide a continuous synthesis method and application of copolymer barrier nylon with simple process, low cost and suitable for industrial production.
[0009] The technical solution adopted by the present invention to solve its technical problems is as follows: a copolymer barrier nylon, comprising the following components: caprolactam, m-phenylenediamine adipate salt, long carbon chain nylon salt, organic coupled nano-montmorillonite and lubricant. The idea of the present invention is to synthesize copolymer nylon by using m-phenylenediamine adipate salt (monomer of MXD6) and caprolactam, and add organic coupled nano-montmorillonite as a barrier component to improve the barrier property of PA6 resin. m-phenylenediamine adipate salt has a very high barrier property, and the barrier property of PA6 can be effectively improved by copolymerizing m-phenylenediamine adipate salt with caprolactam; after copolymerizing m-phenylenediamine adipate salt with caprolactam, there is a disadvantage of low-temperature brittleness. Adding long carbon chain nylon salt introduces tough molecular structural units into the copolymer nylon macromolecular chain, which can make up for the low-temperature brittleness caused by MXD6 salt, and can improve the impact strength or softness of the copolymer of m-phenylenediamine adipate salt and caprolactam. The organic coupled nano-montmorillonite of the present invention is a layered nano-montmorillonite after organic treatment. This nano-montmorillonite has an interlayer distance of 10 to 50 nm. After mixing with caprolactam, caprolactam is adsorbed by organic matter between montmorillonite layers and enters the interlayers, where it reacts to form PA6 macromolecules. This PA6 macromolecule further increases the interlayer distance of the nano-montmorillonite, so that the PA6 polymer also forms a layered structure. This layered structure gives the PA6 resin better gas barrier properties; therefore, the organic coupled nano-montmorillonite can effectively improve the barrier properties of the PA6 resin. The lubricant, as a resin film blowing auxiliary agent, plays a role in lubricating the opening and preventing adhesion. The dispersibility of the lubricant in the PA6 resin will also affect the film blowing process and product quality.
[0010] Preferably, the weight proportions of the components of the copolymer barrier nylon are: 100 parts of caprolactam, 10 to 40 parts of m-phenylenediamine adipate salt, 5 to 20 parts of long carbon chain nylon salt, 0.5 to 2.0 parts of organic coupled nano-montmorillonite, and 0.1 to 0.5 parts of lubricant. Since m-phenylenediamine adipate salt is a monomer of MXD6, considering the cost performance of the barrier resin, the amount of m-phenylenediamine adipate salt is 10 to 40 parts. The larger the amount of long carbon chain nylon salt, the better the flexibility of the copolymer nylon, and vice versa. However, considering the cost performance of the copolymer nylon, the amount of long carbon chain copolymer monomer should be as small as possible. If the amount of organic coupled nano-montmorillonite is too large, although the barrier property is good, the brittleness of the material will increase. On the contrary, its barrier property will decrease and the impact performance of the material will increase. If the amount of lubricant is too large, it may affect the stability of the resin film blowing process, or poor dispersion may form agglomeration, thus affecting the quality and yield of the film. If the amount of lubricant is too small, its lubricating effect is not obvious.
[0011] More preferably, the weight proportions of the copolymer barrier nylon components are: 100 parts of caprolactam, 10-30 parts of m-phenylenediamine adipate, 5-10 parts of long carbon chain nylon salt, 0.5-1.5 parts of organic coupled nano-montmorillonite, and 0.2-0.4 parts of lubricant.
[0012] Preferably, the long carbon chain nylon salt includes one or more of 1010 salt, 1212 salt or 612 salt, etc. The order of softness of the long carbon chain nylon salt is: 1212 salt>612 salt>1010 salt, and more preferably, the long carbon chain nylon salt is 1212 salt and / or 612 salt.
[0013] Preferably, the particle size of the organic coupled nano-montmorillonite is 50-100 nm.
[0014] Preferably, the preparation method of the organic coupled nano-montmorillonite is: after mixing ethanol and a coupling agent, adding nano-montmorillonite under stirring, heating and stirring, filtering, and drying to obtain the organic coupled nano-montmorillonite. The particle size of the nano-montmorillonite is 50-100 nm.
[0015] Preferably, the mass ratio of ethanol, nano-montmorillonite and coupling agent is 10:2-4:0.01-0.10 (more preferably 10:3-4:0.02-0.06). The role of ethanol is to promote the dissolution and dispersion of the coupling agent and the interaction with the nano-montmorillonite. If the amount is too little, the dispersion of the nano-montmorillonite in the solvent will be affected. If the amount is too much, the separation and recovery cost of ethanol is high. The amount of coupling agent has a great influence on the dispersibility of nano-montmorillonite. If the amount of coupling agent added is too small, the surface coating of montmorillonite is imperfect, its dispersibility is poor, and even agglomeration occurs to form insoluble particles, affecting the quality of the film; if the amount of coupling agent added is too large, montmorillonite is easily precipitated. Therefore, the amount of coupling agent used is very important for the dispersion of nano-montmorillonite.
[0016] Preferably, the heating and stirring temperature is 60-80°C (more preferably 60-70°C) and the time is 30-60 minutes (more preferably 30-45 minutes). If the heating temperature is too high, the ethanol vaporization may cause the coupling agent to vaporize, thereby affecting its coupling effect. If the temperature is too low, it will affect the mutual solubility between the coupling agent and ethanol, making it take longer to achieve coupling.
[0017] Preferably, the drying temperature is 100-120° C., and the drying time is 2-4 h (more preferably 2-3 h).
[0018] Preferably, the coupling agent is a silane coupling agent. The silane coupling agent includes one or more of KH550, KH560 or KH570. The surface treatment effect of the coupling agent is: KH550>KH560>KH570, and more preferably, the coupling agent is KH550. Nano-montmorillonite is an inorganic clay that is insoluble in caprolactam. There are two problems with mechanical stirring and dispersion alone: first, uneven dispersion, and second, precipitation occurs, and the re-agglomeration of nanoparticles leads to the generation of inorganic gel particles, which affects the film-forming property of the resin. Therefore, by mixing a silane coupling agent with nano-montmorillonite for surface treatment, the compatibility between nano-montmorillonite and caprolactam can be effectively improved, thereby improving the dispersibility of nano-montmorillonite in caprolactam liquid.
[0019] Preferably, the lubricant includes one or more of silicone, nano-SiO2, erucic acid amide or oleic acid amide, etc. More preferably, the lubricant is a mixture of silicone and erucic acid amide in a mass ratio of 1 to 2:1.
[0020] The technical solution adopted by the present invention to further solve the technical problem is as follows: a continuous synthesis method of copolymer barrier nylon, comprising the following steps:
[0021] (1) Preparing a copolymer salt mixed liquid: adding m-phenylenediamine adipate salt, long carbon chain nylon salt, water, organic coupled nano-montmorillonite and lubricant to a mixed dissolving kettle in sequence, heating and stirring to obtain a copolymer salt mixed liquid, and keeping the mixture warm for later use;
[0022] (2) Prepolymerization: The copolymer salt mixed liquid obtained in step (1) and a portion of caprolactam are continuously pumped into a prepolymerization kettle, heated and stirred for prepolymerization reaction, and drained to obtain a copolymer salt / caprolactam mixed prepolymer liquid;
[0023] (3) Prepolymerization: The copolymer salt / caprolactam mixed prepolymer liquid obtained in step (2) and the remaining caprolactam are pumped into the top of the prepolymerization tube respectively, and flow from top to bottom to the bottom of the prepolymerization tube to carry out prepolymerization reaction to obtain a prepolymer;
[0024] (4) Post-polymerization: pumping the pre-polymer obtained in step (3) into the top of the post-polymerization tube to carry out a post-polymerization reaction to obtain a polymer;
[0025] (5) Post-treatment: After cooling the polymer obtained in step (4), pelletizing, extraction, pre-drying, and solid phase thickening are performed to obtain copolymer barrier nylon.
[0026] Preferably, in step (1), the amount of water used is equivalent to 0.5-1.5:1 (more preferably 0.6-1.2:1) of the total mass of m-phenylenediamine adipate salt and long carbon chain nylon salt.
[0027] Preferably, in step (1), the temperature of the heating and stirring is 80-100°C (more preferably 80-90°C) and the time is 30-60 min (more preferably 30-50 min). If the heating temperature is too low, the solubility of m-phenylenediamine adipate and long carbon chain nylon salt is small. If the heating temperature is too high, part of the water will be vaporized and the dissolving kettle will generate a higher pressure.
[0028] Preferably, in step (2), the amount of caprolactam used is equivalent to 1 / 3 to 1 / 5 of the total amount of caprolactam used. Mixing the copolymer salt with part of the caprolactam is beneficial for the pre-mixing reaction of the copolymer monomer with the caprolactam, which is beneficial for the copolymer monomer to be more evenly dispersed in the caprolactam, and finally the copolymer is evenly distributed in the copolymer macromolecular chain, thereby improving the barrier uniformity of the copolymer nylon.
[0029] Preferably, in step (2), the feed mass ratio of the copolymer salt mixed liquid to caprolactam is 1 to 3:1 (more preferably 1 to 2:1). The larger the feed ratio, the more favorable it is for the dispersion of the comonomers. However, if the feed ratio is too large, the dissolving and mixing kettle must be large, which leads to a longer heating and mixing time and a larger equipment investment.
[0030] Preferably, in step (2), the feed rate of the copolymer salt mixed liquid is 300-600 kg / h, and the feed rate of caprolactam is 200-300 kg / h.
[0031] Preferably, in step (2), the temperature of the heated and stirred prepolymerization reaction is 180-230°C (more preferably 200-230°C), and the residence time is 10-40 min (more preferably 10-30 min). The functions of the prepolymerization reaction are: first, to achieve the mixed dispersion of nylon salt, nano-montmorillonite and caprolactam; second, to achieve the initial polymerization of nylon salt and caprolactam; third, to evaporate part of the excess water through the prepolymerization kettle to reduce the vapor pressure of the prepolymerization tube, so as to maintain the stability of the diamine in the polymerization tube and promote the uniformity of the copolymerization reaction rate.
[0032] Preferably, in step (2), the flow rate of the drainage is 50 to 250 kg / h.
[0033] Preferably, in step (3), the feed mass ratio of the copolymer salt / caprolactam mixed prepolymer liquid to caprolactam is 1 to 6:1 (more preferably 1 to 3:1, and even more preferably 1 to 2:1). If the feed mass ratio of the copolymer salt / caprolactam mixed prepolymer liquid to caprolactam is small, the mixing of the comonomer and caprolactam is more uniform, but the load of the premix will be increased; if the feed ratio is too large, the dispersibility of the comonomer will be affected.
[0034] Preferably, in step (3), the feed rate of the copolymer salt / caprolactam mixed prepolymer liquid is 400-700 kg / h, and the feed rate of the caprolactam is 500-700 kg / h.
[0035] Preferably, in step (3), the temperature of the pre-polymerization reaction is 240-280°C (more preferably 240-250°C), the pressure is 0.1-0.5MPa (more preferably 0.1-0.4MPa), and the residence time is 4-8h (more preferably 4-6h). As the pre-polymerization reaction proceeds, the monomers react to form polymers. The initial reactions on the upper part of the pre-polymerization tube include: first, the hydrolysis and ring-opening reaction of caprolactam, second, the polycondensation reaction between MXD6 salt and long carbon chain nylon salt and aminocaproic acid, third, the condensation reaction between MXD6 salt and long carbon chain nylon salt; fourth, the condensation reaction of MXD6 salt and long carbon chain nylon salt itself. These four reactions have a greater impact on the performance of the final copolymer. Among them, the condensation reaction of MXD6 salt and long carbon chain nylon salt with aminocaproic acid is most beneficial to the barrier properties, mechanical properties and uniformity of the polymer. Therefore, the most important factor affecting the copolymerization reaction is the temperature design at the initial stage of polymerization. At this time, the design of the reaction temperature must promote the hydrolysis reaction of caprolactam and the condensation reaction of MXD6 salt and long carbon chain nylon salt with aminocaproic acid. At a higher temperature, it is conducive to the condensation reaction of MXD6 and long carbon chain nylon salt itself and the mutual auxiliary agent, but the further increase in temperature will cause the MXD6 and long carbon chain nylon segments to be unevenly dispersed in the macromolecular chain, which will lead to uneven barrier properties of the copolymerized nylon. At a lower temperature, it is conducive to the hydrolysis and ring-opening reaction of caprolactam, but the further reduction in temperature makes the hydrolysis and ring-opening reaction of caprolactam faster, and the more aminocaproic acid is produced. The more aminocaproic acid in the reaction system, the faster the condensation reaction between MXD6 salt and long carbon chain nylon salt and aminocaproic acid. Similarly, the vapor pressure of the pre-polymerization tube is also very important for the initial reaction liquid. When the pressure is high, the hydrolysis and ring-opening reaction rate of caprolactam is accelerated, and the diamine in the nylon salt is less vaporized, which is beneficial to the condensation reaction of the copolymer monomer additive. However, the water content of the reaction system is too high, which affects the growth of the molecular weight, that is, the condensation reaction and the molecular weight growth reaction occur simultaneously with the water degradation reaction; when the pressure is low, the diamine will vaporize too much, destroying the balance of the nylon salt in the system, and ultimately affecting the condensation reaction and the molecular weight growth reaction.
[0036] Preferably, in step (4), the feed rate of the prepolymer is 800 to 1200 kg / h.
[0037] Preferably, in step (4), the temperature of the post-polymerization reaction is 240 to 260°C (more preferably 250 to 260°C), the vacuum degree is -0.02 to -0.10MPa (more preferably -0.02 to -0.05MPa), and the residence time is 5 to 9h (more preferably 6 to 8h). The post-polymerization reaction is mainly a molecular chain manufacturing reaction. Properly increasing the reaction temperature is conducive to the formation of macromolecular chains. However, if the temperature is too high, the macromolecular chain degradation reaction liquid will increase. Using appropriate vacuum can remove water molecules in the reaction system, which is conducive to the growth of copolymer molecular chains.
[0038] Preferably, in step (5), the cooling and pelletizing refers to pelletizing by cooling with chilled water at a temperature of -10 to 10°C to 30 to 60°C.
[0039] Preferably, in step (5), the extraction is performed by continuously feeding the pelletized polymer particles into the extraction tower from the top of the extraction tower from top to bottom, and hot water is fed into the extraction tower from bottom to top for extraction.
[0040] Preferably, the extraction temperature is 80-110° C. (more preferably 90-110° C.), the extraction time is 4-8 h (more preferably 6-8 h), and the water-to-material ratio is 2-3:1 (more preferably 2.0-2.5:1).
[0041] Preferably, in step (5), the pre-drying is performed by sending the extracted polymer particles into a pre-drying tower with hot nitrogen and heating them for pre-drying.
[0042] Preferably, the pre-drying temperature is 90 to 120° C. (more preferably 100 to 120° C.) and the time is 3 to 5 hours (more preferably 3 to 4 hours).
[0043] Preferably, in step (5), the solid phase thickening is performed by feeding the pre-dried polymer particles into the solid phase thickening tower from the top of the solid phase thickening tower with hot nitrogen gas to perform solid phase thickening. The solid phase thickening tower is a single tower or multiple towers connected in series.
[0044] Preferably, the solid phase thickening temperature is high first and then low, wherein the temperature of the high temperature section is 100-120°C, the residence time is 6-14h, the temperature of the medium temperature section is 90-110°C, the residence time is 6-8h, and the temperature of the low temperature section is 40-60°C, the residence time is 2-4h. When the solid phase thickening tower is a single tower, the solid phase thickening tower is divided into a high temperature section, a medium temperature section and a low temperature section from top to bottom. When the solid phase thickening tower is a multi-tower series, the solid phase thickening tower is temperature zoned.
[0045] The technical solution adopted by the present invention to further solve the technical problem is as follows: an application of copolymer barrier nylon, wherein the copolymer barrier nylon is applied to food fresh-keeping packaging film.
[0046] The beneficial effects of the present invention are as follows:
[0047] (1) The relative intrinsic viscosity, bending strength and tensile strength of the copolymer barrier nylon of the present invention are similar to those of existing products, while the monomer content is higher than that of pure PA6 and close to that of PA6 / 66; the elongation is nearly 5 times that of MXD6; the unnotched impact strength is 2 to 3 times that of existing products; the oxygen permeability is similar to that of MXD6, which is only half of that of other existing products, indicating that the copolymer barrier nylon of the present invention has high strength, good resistance to cooking, puncture and temperature, and has good barrier properties;
[0048] (2) The method of the present invention has simple process, low cost and is suitable for industrial production;
[0049] (3) The copolymer barrier nylon of the present invention is manufactured by copolymerizing MXD6 salt and caprolactam, and adopts in-situ polymerization of organic coupled nano-montmorillonite, thereby greatly improving the barrier properties of the copolymer nylon. It can replace MXD6 for food packaging film, thus obtaining a cost-effective high-barrier food packaging film material. DETAILED DESCRIPTION
[0050] The present invention will be further described below in conjunction with the embodiments.
[0051] The caprolactam used in the embodiment of the present invention was purchased from Baling Petrochemical, and the 1212 salt was purchased from Yangzi Petrochemical; the nano-montmorillonite used in the embodiment of the present invention was commercially available and had a particle size of 100 nm; the raw materials or chemical reagents used in the embodiment of the present invention, unless otherwise specified, were obtained through conventional commercial channels.
[0052] Reference Example 1 for the preparation method of organically coupled nano-montmorillonite
[0053] After mixing 2000 kg of ethanol and 6 kg of coupling agent KH550, 600 kg of nano-montmorillonite was added under stirring, heated and stirred at 60°C for 30 minutes, filtered, and dried at 120°C for 3 hours to obtain organic coupled nano-montmorillonite 1 (particle size of 100 nm).
[0054] Reference Example 2 for the preparation method of organically coupled nano-montmorillonite
[0055] After mixing 1500 kg of ethanol and 6 kg of coupling agent KH550, 600 kg of nano-montmorillonite was added under stirring, heated and stirred at 60°C for 45 minutes, filtered, and dried at 110°C for 3 hours to obtain organic coupled nano-montmorillonite 2 (particle size of 100 nm).
[0056] Reference Example 3 for the preparation method of organically coupled nano-montmorillonite
[0057] After mixing 1500 kg of ethanol and 6 kg of coupling agent KH550, 600 kg of nano-montmorillonite was added under stirring, heated and stirred at 70°C for 45 minutes, filtered, and dried at 120°C for 2.5 hours to obtain organic coupled nano-montmorillonite 3 (particle size of 100 nm).
[0058] A Copolymer Barrier Nylon Example 1-8
[0059] The components and weight proportions of Examples 1 to 8 of a copolymer barrier nylon are shown in Table 1.
[0060] Table 1 Components and weights of Examples 1 to 8 of a copolymer barrier nylon
[0061]
[0062] Note: The data before and after the “ / ” of caprolactam in the table represent the amount of caprolactam used in steps (2) and (3) respectively; “-” in the table means no addition; 1 part by weight in the table = 79.2 kg.
[0063] A continuous synthesis method of copolymer barrier nylon Example 1
[0064] (1) Preparation of copolymer salt mixed liquid: According to the components and weight parts in Example 1 in Table 1, m-phenylenediamine adipate, 1212 salt, 1350 kg of water, organic coupled nano-montmorillonite and lubricant are added in sequence and mixed and dissolved, heated and stirred at 90° C. for 50 min to obtain copolymer salt mixed liquid, and stored in a tank at 90° C. for standby use;
[0065] (2) Prepolymerization: The copolymer salt mixed liquid obtained in step (1) (feed rate: 305 kg / h) and a portion of caprolactam (feed rate: 300 kg / h) were continuously pumped into a prepolymerization kettle, heated and stirred at 230°C for prepolymerization reaction (residence time: 10 min), and the water was drained at 80 kg / h to obtain a copolymer salt / caprolactam mixed prepolymer liquid;
[0066] (3) Prepolymerization: The copolymer salt / caprolactam mixed prepolymer liquid obtained in step (2) (feed rate: 525 kg / h) and the remaining caprolactam (feed rate: 500 kg / h) were pumped into the top of the prepolymerization tube respectively, and flowed from top to bottom to the bottom of the prepolymerization tube, and prepolymerization reaction was carried out at 240°C and 0.4 MPa (residence time: 6 h) to obtain a prepolymer;
[0067] (4) Post-polymerization: The pre-polymer obtained in step (3) was pumped into the top of the post-polymerization tube by a melt pump at a rate of 1000 kg / h, and a post-polymerization reaction was carried out at 260° C. and −0.05 MPa (residence time was 8 h) to obtain a polymer;
[0068] (5) Post-treatment: The polymer obtained in step (4) is cooled in a cooling tank through a die head injection belt, and then sent to a pelletizer for pelletizing, extraction, pre-drying, and solid phase viscosity enhancement to obtain copolymer barrier nylon; the cooling pelletizing refers to pelletizing by cooling with chilled water at a temperature of -10°C to 30°C; the extraction is to continuously feed the pelletized polymer particles from the top of the extraction tower to the extraction tower from top to bottom, and hot water is fed from bottom to top (water-to-material ratio is 2.5:1), and the extraction is carried out at 110°C for 8 hours to obtain the product; the pre-drying is to feed the extracted polymer particles into a pre-drying tower with hot nitrogen, and heat and pre-dry them at 120°C for 3 hours h, that is, the solid phase thickening is to send the pre-dried polymer particles into the solid phase thickening tower 1 from the top of the solid phase thickening tower 1 with hot nitrogen from top to bottom for solid phase thickening, and the temperature distribution is: 120°C at the top, 120°C in the middle, 110°C at the bottom, and the residence time is 8h (this tower is a high temperature section), and then the solid phase thickening tower 1 is sent to the top of the solid phase thickening tower 2 by wind from the bottom, and further thickening reaction is carried out, and the heating temperature distribution is: 110°C at the top (high temperature section) for a residence time of 6h, 100°C in the middle (medium temperature section) for a residence time of 6h, 60°C at the bottom (low temperature section) for a residence time of 2h, and the copolymer barrier nylon is obtained.
[0069] A continuous synthesis method of copolymer barrier nylon Example 2
[0070] (1) Preparation of copolymer salt mixed liquid: According to the components and weight parts in Example 2 in Table 1, m-phenylenediamine adipate, 1212 salt, 1674 kg of water, organic coupled nano-montmorillonite and lubricant are added in sequence and mixed and dissolved, heated and stirred at 80° C. for 45 min to obtain copolymer salt mixed liquid, and stored in a tank at 80° C. for standby use;
[0071] (2) Prepolymerization: The copolymer salt mixed liquid obtained in step (1) (feed rate: 378 kg / h) and a portion of caprolactam (feed rate: 300 kg / h) were continuously pumped into a prepolymerization kettle, heated and stirred at 210°C for prepolymerization reaction (residence time: 20 min), and drained at 180 kg / h to obtain a copolymer salt / caprolactam mixed prepolymer liquid;
[0072] (3) Prepolymerization: The copolymer salt / caprolactam mixed prepolymer liquid obtained in step (2) (feed rate: 578 kg / h) and the remaining caprolactam (feed rate: 500 kg / h) were pumped into the top of the prepolymerization tube respectively, and flowed from top to bottom to the bottom of the prepolymerization tube, and prepolymerization reaction was carried out at 250°C and 0.2 MPa (residence time: 4 h) to obtain a prepolymer;
[0073] (4) Post-polymerization: The pre-polymer obtained in step (3) was pumped into the top of the post-polymerization tube by a melt pump at a rate of 1000 kg / h, and a post-polymerization reaction was carried out at 250° C. and −0.03 MPa (residence time was 7 h) to obtain a polymer;
[0074] Step (5) is the same as in Example 1.
[0075] A continuous synthesis method of copolymer barrier nylon Example 3
[0076] (1) Preparation of copolymer salt mixed liquid: According to the components and weight parts in Example 3 in Table 1, m-phenylenediamine adipate, 1212 salt, 1998 kg of water, organic coupled nano-montmorillonite and lubricant are added in sequence and mixed and dissolved, heated and stirred at 85° C. for 40 min to obtain copolymer salt mixed liquid, and stored in a tank at 85° C. for standby use;
[0077] (2) Prepolymerization: The copolymer salt mixed liquid obtained in step (1) (feed rate: 450 kg / h) and a portion of caprolactam (feed rate: 300 kg / h) are continuously pumped into a prepolymerization kettle, heated and stirred at 220°C for prepolymerization reaction (residence time: 15 min), and the water is discharged at 180 kg / h to obtain a copolymer salt / caprolactam mixed prepolymer liquid;
[0078] (3) Prepolymerization: The copolymer salt / caprolactam mixed prepolymer liquid obtained in step (2) (feed rate: 570 kg / h) and the remaining caprolactam (feed rate: 500 kg / h) were pumped into the top of the prepolymerization tube respectively, and flowed from top to bottom to the bottom of the prepolymerization tube, and prepolymerization reaction was carried out at 245°C and 0.3 MPa (residence time: 5 h) to obtain a prepolymer;
[0079] (4) Post-polymerization: The pre-polymer obtained in step (3) was pumped into the top of the post-polymerization tube by a melt pump at a rate of 1000 kg / h, and a post-polymerization reaction was carried out at 255° C. and −0.04 MPa (residence time was 6 h) to obtain a polymer;
[0080] Step (5) is the same as in Example 1.
[0081] A continuous synthesis method of copolymer barrier nylon Example 4
[0082] (1) Preparation of copolymer salt mixed liquid: According to the components and weight parts in Example 4 in Table 1, m-phenylenediamine adipate, 1212 salt, 2322 kg of water, organic coupled nano-montmorillonite and lubricant are added in sequence and mixed and dissolved, heated and stirred at 90° C. for 50 min to obtain copolymer salt mixed liquid, and stored in a tank at 90° C. for standby use;
[0083] (2) Prepolymerization: The copolymer salt mixed liquid obtained in step (1) (feed rate: 523.6 kg / h) and a portion of caprolactam (feed rate: 300 kg / h) were continuously pumped into a prepolymerization kettle, heated and stirred at 230°C for prepolymerization reaction (residence time: 10 min), and the water was drained at 210 kg / h to obtain a copolymer salt / caprolactam mixed prepolymer liquid;
[0084] (3) Prepolymerization: The copolymer salt / caprolactam mixed prepolymer liquid obtained in step (2) (feed rate: 613.6 kg / h) and the remaining caprolactam (feed rate: 500 kg / h) were pumped into the top of the prepolymerization tube respectively, and flowed from top to bottom to the bottom of the prepolymerization tube, and prepolymerization reaction was carried out at 240°C and 0.4 MPa (residence time: 6 h) to obtain a prepolymer;
[0085] Steps (4) and (5) are the same as those in Example 1.
[0086] A continuous synthesis method of copolymer barrier nylon Example 5
[0087] The difference between this embodiment and embodiment 3 is that the operation is carried out according to the components and weight parts in embodiment 5 in Table 1. The rest is the same as embodiment 3.
[0088] A continuous synthesis method of copolymer barrier nylon Example 6
[0089] (1) Preparation of copolymer salt mixed liquid: According to the components and weight parts in Example 6 in Table 1, m-phenylenediamine adipate, 612 salt, 2250 kg of water, organic coupled nano-montmorillonite and lubricant are added in sequence and mixed and dissolved, heated and stirred at 90° C. for 50 min to obtain copolymer salt mixed liquid, and stored in a tank at 90° C. for standby use;
[0090] (2) Prepolymerization: The copolymer salt mixed liquid obtained in step (1) (feed rate: 509 kg / h) and a portion of caprolactam (feed rate: 300 kg / h) were continuously pumped into a prepolymerization kettle, heated and stirred at 230°C for prepolymerization reaction (residence time: 10 min), and drained at 203 kg / h to obtain a copolymer salt / caprolactam mixed prepolymer liquid;
[0091] (3) Prepolymerization: The copolymer salt / caprolactam mixed prepolymer liquid obtained in step (2) (feed rate: 606 kg / h) and the remaining part of caprolactam (feed rate: 500 kg / h) were pumped into the top of the prepolymerization tube respectively, and flowed from top to bottom to the bottom of the prepolymerization tube, and prepolymerization reaction was carried out at 240°C and 0.4 MPa (residence time: 6 h) to obtain a prepolymer;
[0092] Steps (4) and (5) are the same as those in Example 1.
[0093] A continuous synthesis method of copolymer barrier nylon Example 7
[0094] The difference between this embodiment and embodiment 6 is that the operation is carried out according to the components and weight parts in Table 1 of embodiment 7. The rest is the same as embodiment 6.
[0095] A continuous synthesis method of copolymer barrier nylon Example 8
[0096] The difference between this embodiment and embodiment 6 is that the operation is carried out according to the components and weight parts in embodiment 8 in Table 1. The rest is the same as embodiment 6.
[0097] Application Examples 1 to 8 of Copolymer Barrier Nylon
[0098] The copolymer barrier nylon described in Examples 1 to 8 is respectively applied to food fresh-keeping packaging film.
[0099] Comparative Examples 1-2
[0100] The difference between this comparative example and Example 1 is that the operation is carried out according to the components and weight parts in Comparative Examples 1 and 2 in Table 1, respectively. The rest is the same as Example 1.
[0101] In order to investigate the technical effect of the copolymer barrier nylon obtained in Examples 1 to 8 of the present invention, MXD6 (Mitsubishi, Japan), PA6 (Baling Petrochemical 3400), PA6 / 66 copolymer resin (Remifu 3350), and Comparative Examples 1 to 2 were selected for comparative testing. Product performance testing and standards: relative intrinsic viscosity: GB2006.1-89, monomer content%: GB / T14966-94, flexural strength MPa: ASTM D790, tensile strength MPa: ASTM D638, elongation%: ASTM D638, unnotched impact strength kJ / m 2 : ASTM D256, oxygen transmission rate cm 3 / (m 2 ·24h·0.1MPa): The copolymer nylon obtained in the examples of the present invention and the comparative examples and the MXD6, PA6, and PA6 / 66 copolymer resins were melt-extruded and blown into films at melt extrusion temperatures of 250, 255, 260, and 280°C, with a film thickness of 20 μm. The oxygen permeability was then tested according to GB T19789-2005; the results are shown in Table 2.
[0102] Table 2 Performance comparison of the copolymer barrier nylon obtained in Examples 1 to 8 of the present invention, Comparative Examples 1 and 2, and existing products
[0103]
[0104] As shown in Table 2, the relative intrinsic viscosity, bending strength and tensile strength of the copolymer barrier nylon obtained in Examples 1 to 8 of the present invention are similar to those of existing products, while the monomer content is higher than that of pure PA6 and close to that of PA6 / 66; the elongation is nearly 5 times that of MXD6, which is due to the addition of long carbon chain comonomers to improve the toughness of the resin; the unnotched impact strength is 2 to 3 times that of existing products; the oxygen permeability is similar to that of MXD6, which is only half of that of other existing products, because the addition of m-phenylenediamine adipate and organic coupled nano-montmorillonite effectively improves the barrier properties of nylon; Comparative Examples 1 and 2 also fully demonstrate the contribution of m-phenylenediamine adipate and organic nano-coupled montmorillonite to the barrier properties. In summary, the copolymer barrier nylon obtained in Examples 1 to 8 of the present invention has high strength, good resistance to cooking, puncture and temperature, and has good barrier properties.
Claims
1. A copolymer barrier nylon, characterized in that: The invention comprises the following components and weight parts: 100 parts of caprolactam, 15-40 parts of m-phenylenediamine adipate salt, 5-10 parts of long carbon chain nylon salt, 1.0-2.0 parts of organic coupled nano-montmorillonite, and 0.1-0.5 parts of lubricant; the preparation method of the organic coupled nano-montmorillonite comprises: mixing ethanol and a coupling agent, adding nano-montmorillonite under stirring, heating and stirring, filtering, and drying to obtain the organic coupled nano-montmorillonite; the mass ratio of the ethanol, nano-montmorillonite and coupling agent is 10:2-4:0.01-0.06; the heating and stirring temperature is 60-80°C, and the time is 30-60 minutes; The continuous synthesis method of the copolymer barrier nylon comprises the following steps: (1) Preparing a copolymer salt mixed liquid: adding m-phenylenediamine adipate salt, long carbon chain nylon salt, water, organic coupled nano-montmorillonite and lubricant to a mixed dissolving kettle in sequence, heating and stirring to obtain a copolymer salt mixed liquid, and keeping the mixture warm for later use; (2) Prepolymerization: the copolymer salt mixed liquid obtained in step (1) and a portion of caprolactam are continuously pumped into a prepolymerization kettle, heated and stirred for prepolymerization reaction, and drained to obtain a copolymer salt / caprolactam mixed prepolymer liquid; the amount of caprolactam used is equivalent to 1 / 3 to 1 / 5 of the total amount of caprolactam used; the feed mass ratio of the copolymer salt mixed liquid to caprolactam is 1 to 3:1; the temperature of the heated and stirred prepolymerization reaction is 180 to 230° C., and the residence time is 10 to 40 min; (3) Prepolymerization: The copolymer salt / caprolactam mixed prepolymer liquid obtained in step (2) and the remaining caprolactam are pumped into the top of the prepolymerization tube respectively, and flow from top to bottom to the bottom of the prepolymerization tube to carry out a prepolymerization reaction to obtain a prepolymer; the feed mass ratio of the copolymer salt / caprolactam mixed prepolymer liquid to the caprolactam is 1 to 6:1; the prepolymerization reaction temperature is 240 to 280° C., the pressure is 0.1 to 0.5 MPa, and the residence time is 4 to 8 hours; (4) Post-polymerization: pumping the pre-polymer obtained in step (3) into the top of the post-polymerization tube to carry out a post-polymerization reaction to obtain a polymer; the post-polymerization reaction temperature is 240 to 260° C., the vacuum degree is -0.02 to -0.10 MPa, and the residence time is 5 to 9 hours; (5) Post-treatment: After cooling the polymer obtained in step (4), pelletizing, extraction, pre-drying, and solid phase thickening are performed to obtain copolymer barrier nylon.
2. The copolymer barrier nylon according to claim 1, characterized in that: The weight proportions of the components are as follows: the long carbon chain nylon salt includes one or more of 1010 salt, 1212 salt or 612 salt; the particle size of the organic coupled nano-montmorillonite is 50-100 nm; the drying temperature is 100-120° C., and the drying time is 2-4 hours; the coupling agent is a silane coupling agent; and the lubricant includes one or more of silicone, nano-SiO2, erucamide or oleamide.
3. The copolymer barrier nylon according to claim 1 or 2, characterized in that: In step (1), the amount of water used is equivalent to 0.5-1.5:1 of the total mass of m-phenylenediamine adipate salt and long carbon chain nylon salt; the temperature of the heating and stirring is 80-100° C., and the time is 30-60 min.
4. The copolymer barrier nylon according to claim 1 or 2, characterized in that: In step (2), the feed rate of the copolymer salt mixed liquid is 300-600 kg / h, the feed rate of caprolactam is 200-300 kg / h; and the flow rate of the drainage is 50-250 kg / h.
5. The copolymer barrier nylon according to claim 3, characterized in that: In step (2), the feed rate of the copolymer salt mixed liquid is 300-600 kg / h, the feed rate of caprolactam is 200-300 kg / h; and the flow rate of the drainage is 50-250 kg / h.
6. The copolymer barrier nylon according to claim 1 or 2, characterized in that: In step (3), the feed rate of the copolymer salt / caprolactam mixed prepolymer liquid is 400-700 kg / h, and the feed rate of the caprolactam is 500-700 kg / h.
7. The copolymer barrier nylon according to claim 3, characterized in that: In step (3), the feed rate of the copolymer salt / caprolactam mixed prepolymer liquid is 400-700 kg / h, and the feed rate of the caprolactam is 500-700 kg / h.
8. The copolymer barrier nylon according to claim 4, characterized in that: In step (3), the feed rate of the copolymer salt / caprolactam mixed prepolymer liquid is 400-700 kg / h, and the feed rate of the caprolactam is 500-700 kg / h.
9. The copolymer barrier nylon according to claim 1 or 2, characterized in that: In step (4), the feed rate of the prepolymer is 800 to 1200 kg / h.
10. The copolymer barrier nylon according to claim 3, characterized in that: In step (4), the feed rate of the prepolymer is 800 to 1200 kg / h.
11. The copolymer barrier nylon according to claim 4, characterized in that: In step (4), the feed rate of the prepolymer is 800 to 1200 kg / h.
12. The copolymer barrier nylon according to claim 6, characterized in that: In step (4), the feed rate of the prepolymer is 800 to 1200 kg / h.
13. The copolymer barrier nylon according to claim 1 or 2, characterized in that: In step (5), the cooling pelletizing refers to pelletizing by cooling with chilled water at a temperature of -10 to 10°C to 30 to 60°C; the extraction refers to continuously feeding the pelletized polymer particles from the top of the extraction tower into the extraction tower from top to bottom, and feeding hot water from bottom to top for extraction; the extraction temperature is 80 to 110°C, the time is 4 to 8 hours, and the water-to-material ratio is 2 to 3:1; the pre-drying refers to feeding the extracted polymer particles into the pre-drying tower with hot nitrogen for heating and pre-drying; the pre The drying temperature is 90-120°C and the time is 3-5h; the solid phase thickening is to send the pre-dried polymer particles into the solid phase thickening tower from the top of the solid phase thickening tower with hot nitrogen from top to bottom for solid phase thickening; the solid phase thickening temperature is high at first and then low, wherein the temperature of the high temperature section is 100-120°C and the residence time is 6-14h, the temperature of the medium temperature section is 90-110°C and the residence time is 6-8h, and the temperature of the low temperature section is 40-60°C and the residence time is 2-4h.
14. The copolymer barrier nylon according to claim 3, characterized in that: In step (5), the cooling pelletizing refers to pelletizing by cooling with chilled water at a temperature of -10 to 10°C to 30 to 60°C; the extraction refers to continuously feeding the pelletized polymer particles from the top of the extraction tower into the extraction tower from top to bottom, and feeding hot water from bottom to top for extraction; the extraction temperature is 80 to 110°C, the time is 4 to 8 hours, and the water-to-material ratio is 2 to 3:1; the pre-drying refers to feeding the extracted polymer particles into the pre-drying tower with hot nitrogen for heating and pre-drying; the pre The drying temperature is 90-120°C and the time is 3-5h; the solid phase thickening is to send the pre-dried polymer particles into the solid phase thickening tower from the top of the solid phase thickening tower with hot nitrogen from top to bottom for solid phase thickening; the solid phase thickening temperature is high at first and then low, wherein the temperature of the high temperature section is 100-120°C and the residence time is 6-14h, the temperature of the medium temperature section is 90-110°C and the residence time is 6-8h, and the temperature of the low temperature section is 40-60°C and the residence time is 2-4h.
15. The copolymer barrier nylon according to claim 4, characterized in that: In step (5), the cooling pelletizing refers to pelletizing by cooling with chilled water at a temperature of -10 to 10°C to 30 to 60°C; the extraction refers to continuously feeding the pelletized polymer particles from the top of the extraction tower into the extraction tower from top to bottom, and feeding hot water from bottom to top for extraction; the extraction temperature is 80 to 110°C, the time is 4 to 8 hours, and the water-to-material ratio is 2 to 3:1; the pre-drying refers to feeding the extracted polymer particles into the pre-drying tower with hot nitrogen for heating and pre-drying; the pre The drying temperature is 90-120°C and the time is 3-5h; the solid phase thickening is to send the pre-dried polymer particles into the solid phase thickening tower from the top of the solid phase thickening tower with hot nitrogen from top to bottom for solid phase thickening; the solid phase thickening temperature is high at first and then low, wherein the temperature of the high temperature section is 100-120°C and the residence time is 6-14h, the temperature of the medium temperature section is 90-110°C and the residence time is 6-8h, and the temperature of the low temperature section is 40-60°C and the residence time is 2-4h.
16. The copolymer barrier nylon according to claim 6, characterized in that: In step (5), the cooling pelletizing refers to pelletizing by cooling with chilled water at a temperature of -10 to 10°C to 30 to 60°C; the extraction refers to continuously feeding the pelletized polymer particles from the top of the extraction tower into the extraction tower from top to bottom, and feeding hot water from bottom to top for extraction; the extraction temperature is 80 to 110°C, the time is 4 to 8 hours, and the water-to-material ratio is 2 to 3:1; the pre-drying refers to feeding the extracted polymer particles into the pre-drying tower with hot nitrogen for heating and pre-drying; the pre The drying temperature is 90-120°C and the time is 3-5h; the solid phase thickening is to send the pre-dried polymer particles into the solid phase thickening tower from the top of the solid phase thickening tower with hot nitrogen from top to bottom for solid phase thickening; the solid phase thickening temperature is high at first and then low, wherein the temperature of the high temperature section is 100-120°C and the residence time is 6-14h, the temperature of the medium temperature section is 90-110°C and the residence time is 6-8h, and the temperature of the low temperature section is 40-60°C and the residence time is 2-4h.
17. The copolymer barrier nylon according to claim 9, characterized in that: In step (5), the cooling pelletizing refers to pelletizing by cooling with chilled water at a temperature of -10 to 10°C to 30 to 60°C; the extraction refers to continuously feeding the pelletized polymer particles from the top of the extraction tower into the extraction tower from top to bottom, and feeding hot water from bottom to top for extraction; the extraction temperature is 80 to 110°C, the time is 4 to 8 hours, and the water-to-material ratio is 2 to 3:1; the pre-drying refers to feeding the extracted polymer particles into the pre-drying tower with hot nitrogen for heating and pre-drying; the pre The drying temperature is 90-120°C and the time is 3-5h; the solid phase thickening is to send the pre-dried polymer particles into the solid phase thickening tower from the top of the solid phase thickening tower with hot nitrogen from top to bottom for solid phase thickening; the solid phase thickening temperature is high at first and then low, wherein the temperature of the high temperature section is 100-120°C and the residence time is 6-14h, the temperature of the medium temperature section is 90-110°C and the residence time is 6-8h, and the temperature of the low temperature section is 40-60°C and the residence time is 2-4h.
18. An application of the copolymer barrier nylon according to any one of claims 1 to 17, characterized in that: The copolymer barrier nylon according to any one of claims 1 to 17 is applied to food fresh-keeping packaging film.
Citation Information
Patent Citations
High-shrinkage biaxially-oriented nylon 6 film with hot shrinkage reaching 8-10% and manufacture method thereof
CN106832907A
Antibacterial high-barrier nylon film and preparation method thereof
CN110641107A
High-barrier nylon blending material
CN113881221A
Continuous synthesis method of impact-resistant obstructed copolymerized nylon resin and application thereof
CN109535415A